Different physiological and biochemical responses in maize hybrids subjected to drought stress at vegetative and reproductive stages - Goodarzian-Ghahfarokhii, Maryam; Mansouri-Far, Cyrus; Saeidi, Mohsen; Abdoli, Majid (Acta Biologica Szegediensis, 2016)
The growth and development of all plants are seriously limited by a variety of environmental stresses. In this study, responses in crop yield, physiological and biochemical traits were investigated in maize (Zea mays L.) hybrids such as SC704, SC700 (FAO 700), SC647 (FAO 600), SC500 (FAO 500), SC370 (FAO 300) and SC260 (FAO 200) subjected to drought stress induced by stopping irrigation at vegetative stage (4-5 leaves) and reproductive stage (anthesis). The results showed that drought stress had a significant effect on these characteristics. The yield and its components decreased considerably under water stress: the main factors that caused reduction of yield were the decrease in the number of grain per ear and 1000-grain weight. Reduction of yield in short maturity hybrids was higher than in other ones. Activity of superoxide dismutase (SOD) as well as permeability of plasma membrane increased significantly, but ascorbate peroxidase (APX) activity decreased under water stress. Maximum quantum efficiency of PSII (Fv/Fm) and performance index (PI) revealed a significant reduction in leaves in comparison with control plants. The content of soluble proteins in leaves reduced with increasing drought stress. These results suggested that water stress lead to the production of reactive oxygen species (ROS), which caused an increased membrane permeability and oxidative stress in the maize plants. Furthermore, maize hybrids with higher levels of antioxidant enzyme activities showed higher resistance to drought stress and produced higher yield under stress. So that SC704 and SC700 were the most tolerant, however, SC647 and SC500 were drought semi-tolerant to water stress, and SC370 and SC260 were the most sensitive.